Mandibular fractures in partially edentulous patients. Closed treatment alternatives. A Cases series - Contreras, Carlos (2023)
For the treatment of mandibular fractures, there are protocols whose primary purpose is early function. However, several reasons prevent the execution of these techniques in Venezuela, mainly due to economic problems regarding the acquisition of specialized osteosynthesis materials. As a result, there is a necessity to resort to old surgical techniques. A study with a descriptive longitudinal design is presented, reporting 5 clinical cases of jaw fractures with the following inclusion criteria: presenting a mandibular fracture in partially dentate patients with impossibility of accessing the osteosynthesis material of the load-bearing system. The treatment conducted under closed surgical procedures. The condition of partial edentulism confers instability to the mandible fracture, hindering anatomical reduction and causing a loss of vertical and transverse dimension. These issues are addressed through the utilization of modified Gunning-type splints, which help in recovery. The splints were maintained in position with circum-mandibular and circum-zygomatic bone suspension wiring as a means to establish stability over time. Satisfactory results were obtained, indicating that these techniques can still be considered as treatment options today.